Primary transmissible venereal tumour in the nasal cavity of two dogs - Mohamed Mustapha, Noordin; Sabri, Jasni; Mohd Lila, Mohd Azmi; Arshad, Habibah (Veterinary Association Malaysia, 2004)
Transmissible venereal tumour (TVT) is a common tumour affecting dogs especially strays. Usually, the external genitalia is most frequently affected. Although there are reports of extra-genitalia TVT (usually secondary), incidence in the nasal cavity as a primary tumour is extremely rare. This paper describes the presence of primary TVT in the nasal cavity of two dogs along with the postulated pathogenesis. It also warrants clinicians to consider this tumour as one of the differentials for prolonged nasal discharge and nasal neoplasm.